Anterior capsulotomy and accumbensotomy of obsessive-compulsive disorder with obsessional slowness: a case report - Lai, Rui; Pang, Xiao; Ming, Yang; He, Haiping; Xiong, Yu; You, Jian; Chen, Ligang; Gong, Feilong (Frontiers in Psychiatry, 2024)
Obsessional slowness (OS) is characterized by a syndrome of extreme slowness in doing ordinary, day-to-day activities. Several scholars regarded OS as secondary to obsessive compulsive disorder (OCD). Therefore, it is commonly thought to be the consequence of extensive rituals and has been paid minimal attention in its own right. A combination of behavior therapy and aromatherapy are recommended for treatment of this condition. However, the outcome is often frustrating. Reports of surgical management for OS are limited. Patient concerns:She had symptoms characterized by repeated checking and progressive slowness in self-care behavior. Diagnosis:At the age of 19, the patient had the first presentation. The patient was diagnosed with a case of OCD with obsessional slowness according to the International Classification of Diseases and Related Health Problems (ICD-10).Interventions:Considering the lack of a response to pharmacotherapy and cognitive behavioral therapy (CBT), we treated this case with anterior capsulotomy and accumbensotomy. Outcomes: Moderate somnolence, urticaria, juvenile behavior, mild short-term memory impairment and slight nonsense were noted during the first postoperative days. At 10 months, the patient’s OCD symptoms recovered nearly to her preoperative level. The OS symptom also had an obvious rebound at 10 months. Through comprehensive judgment, we decided to choose accumbensotomy. At 9 months after the accumbensotomy, the OCD symptoms started to rebound. Soon after, the OS symptoms also recurred. At the last timepoint of 30 months, the patient’s OCD and OS symptoms had completely rebounded. This time, the patient and parents refused any treatment. Conclusion: This case suggests that OCD with OS, as a special category, might not be suitable for stereotactic neurosurgery. Furthermore, multiple surgeries in this kind of OCD patient should be considered with as much caution as much as possible.